Website Training for Democracy Enhancement - Mukhammad Soleh; Dian Utami Ikhwaningrum; Sinda Eria Ayuni; Marsudi Dedi Putra; Bayu Firmanto; Galih Setiyo Refangga; Sigid Budi Santoso; Intan Rachmawati; Imaniar Juang Hayati; Sulistya Diah Paramitha; Aghniya Ariza Sa’adah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Website is a means to realize E-Government. Village E-Government is the implementation of village government through the use of websites, which is very important as a means of democracy and village government accountability for governance. The method used is to conduct training for Sukopuro village officials who are responsible for managing the website. The training included an introduction to creating the email, creating a Google form, and an introduction to how to accommodate community input from the Google form to the Sukopuro Village Government website. The results of this activity were very positive and received a good response from the village because it added knowledge and skills in organizing the web and creating Google forms as a means of community democracy and village development, in the framework of implementing the Sukopuro Village Government website. The understanding of village officials in Sukopuro Village about the website increased from 20% to 80%. Communities have the opportunity to increase their democracy in village development and stipulate of village government public policies through the Google form and website in the village.